A mechanism model of the effect of hedonic product consumption on well-being - Zhong, Jing Yang; Mitchell, Vincent-Wayne (Journal of consumer psychology, 2010)
In response to recent calls for research into activities that may increase happiness, this study uses longitudinal data to investigate changes in within-subject, instead of between-subject, well-being. In the context of hedonic product consumption, this study reveals a mechanism by which consumption influences well-being through the mediating effect of satisfaction with associated life domains. Four years of data from a large national panel survey show that consuming hedonic products has indirect effects on well-being, by improving consumers' satisfaction within relevant life domains. High hedonic consumption improves satisfaction with relevant life domains, primarily through more frequent consumption of low-cost hedonic products rather than less frequent consumption of high-cost hedonic products.